PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PT. NIRO FACTORY OUTLET GUNUNG PUTRI BOGOR - Arief Syah Safrianto; Anita (Jurnal Manajemen Bisnis Krisnadwipayana, 2024)
The purpose at analyze the effect of brand image and product quality on customer satisfaction at PT. Niro Factory Outlet Gunung Putri Bogor. This research is included in the category of causal associative research using a quantitative approach. The population in this study were customers the Niro Factory Outlet., By using the Slovin formula, the sample in this study. The technique used for sampling is simple random sampling. The analytical method uses simultaneous and partially linear regression analysis. The results of the research show that in simultaneous and partially ways brand image and product quality have a positive and significant effect on the customer satisfaction at PT. Niro Factory Outlet Gunung Putri Bogor.